OPTIMAL THERMAL SENSORS PLACEMENT BASED ON INDOOR THERMAL ENVIRONMENT CHARACTERIZATION BY USING CFD MODEL - Faridah,; Sesotya Utami, Sentagi; Jaya Yanti, Ressy; Sunarno,; Nurjani, Emilya; Wijaya, Rony (Journal of Applied Engineering Science, 2021)
This paper discusses analysis to obtain the optimal thermal sensors placement based on indoor thermal characteristics. The method relies on the CFD simulation by manipulating the outdoor climate and indoor air conditioning (AC) system. First, the alternative sensor's position considered the optimum installation and the occupant's safety. Utilizing the Standardized Euclidean Distance analysis, these positions are then selected for the best position using the distribution of the thermal parameters' values data at the activity zones. On-site measurement validated the CFD model results with the maximum RMSE between both data sets as 0.76 °C for temperature, the relative humidity of 3.67, and an air velocity of 0.08 m/s2, due to the significant effect of the building location. The SED analysis results are the optimum sensor positions that accurately, consistently, and have the optimum % coverage representing the thermal condition at 1,1m floor level. The positions are B5 for R15, position D4 for R33, and position B6 for R40. At these positions, actual sensors are installed and proven to be valid results since sensors could detect thermal variables at the height of 1.1 m with SED validation values of 0.76 °C, 3.67, and dan 0.08 m/s2, for R15, R33, and R40, respectively.
Keywords: sensor placement; indoor thermal environment; euclidean distance; CFD model; monitoring system